The Culture of Active Citizenship as the Reason of Social Life - Stanisław Chrobak (Nicolaus Copernicus University in Toruń, 2017)
In the course of the transformations that take place in life, events that become part of a human being, fit into the history of his life, and identify important areas of his activity and commitment. The diverse memberships (family, territorial, class, religious, national) are not an obstacle but an abundance. Citizenship is a set of rights and obligations, and being a citizen in society means accepting its rules. The true human community is where the person finds himself through the gift of himself and the ability to accept the gift of another person. The whole meaning of the so-called worldly human life then only gains value when all that a man does now is merely the beginning of the "fulfilment" and achievement of the human person in his personal file.